1983
DOI: 10.1007/bf02043479
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic epilepsy: Review of a series and proposed classification and etiopathogenesis

Abstract: A review of the convulsive seizures of 153 alcoholics is followed by a proposed classification with the aim of defining more precisely the pattern of so-called alcoholic epilepsy and distinguishing it from the other alcohol-related seizures (due to sudden changes in alcohol intake: convulsive inebriation or alcohol withdrawal seizures) and seizures in which alcohol is only one of the pathogenetic factors. Particular attention is devoted to an analysis and comparison of alcohol withdrawal seizures and alcoholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
5

Year Published

1985
1985
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
1
29
0
5
Order By: Relevance
“…The literature in this field suffers from the lack of a unanimous definition,41 42 which makes the reproducibility of results difficult. Whereas the withdrawal seizure is closely linked to cessation or abrupt reduction of an increased alcohol intake,14 other alcohol related seizures may not be directly related to a drinking bout 5.…”
Section: Discussionmentioning
confidence: 99%
“…The literature in this field suffers from the lack of a unanimous definition,41 42 which makes the reproducibility of results difficult. Whereas the withdrawal seizure is closely linked to cessation or abrupt reduction of an increased alcohol intake,14 other alcohol related seizures may not be directly related to a drinking bout 5.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is not mentioned in the ICE (Commission, 1989), alcoholic epilepsy represents a real syndrome, defined as ''recurrent seizures occurring in alcoholics not previously epileptic, not suffering from other potentially epileptogenic diseases and not related to either a sudden withdrawal or massive intake of alcohol" (Devetag et al, 1983), or "recurrent unprovoked seizures without obvious antecedents, developing after the onset of drinking and unrelated to withdrawal" (Hauser et al, 1988). Some adult patients with an isolated seizure will later develop alcoholic epilepsy.…”
Section: Crypto-symptopathic Genic Maticmentioning
confidence: 99%
“…Cerebral atrophy as determined by computer tomography (CT) has shown no differences between those alcoholics with seizures and those without [33]-Devetag et al [34] have reported essentially different findings from those of others, although they are in agreement with another substantial series [35] that very roughly io% of all alcoholics experience seizures at some time. Of Devetag's large series of x435 patients, x53 had a history of seizures.…”
Section: Alcohol and Seizuresmentioning
confidence: 71%